Football Skills of Students of Syekh Yusuf Gowa Football School Reviewed from Cardiovascular Endurance - Awaluddin, Awaluddin (Sains Global Institut, Indonesia, 2024)
This study aims to determine the Football Skills of Syekh Yusuf Gowa Football School Students Reviewed from Cardiovascular Endurance. This type of research is a descriptive research type. The population in this study were all Syekh Yusuf Gowa Football athletes with a research sample of 20 people aged 13-15 years. The sampling technique was by using